High-strength foaming shoe material and preparation method thereof
By using EVA, polyether block polyamide, EVA-g-MAH, polyurea and reinforcing fiber in foamed shoes, combined with supercritical foaming technology, the problem of high permanent deformation rate of shoe materials is solved. Improves resilience and tear strength, achieving higher mechanical properties.
Patent Information
- Application Number
- CN202411391823.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-08
AI Technical Summary
Existing foamed shoes are prone to wrinkles and deformation during use, mainly because their compression permanent deformation rate is too large, and their fatigue resistance and elasticity need to be improved.
Using the combination of EVA elastomer, polyether block polyamide elastomer, EVA-g-MAH elastomer, polyurea elastomer and reinforced fiber, through supercritical foaming technology, combined with nucleating agents such as nanotitanium dioxide and nano zinc oxide. , the injection machine and twin screw extruder are used to granulate to form high-strength foamed shoe materials.
It improves the elasticity and tear strength of foamed shoes, reduces the compression permanent deformation rate, allows the shoes to maintain elasticity and flexibility at low temperatures, and enhances mechanical strength and toughness.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of foamed shoe materials, and particularly relates to a high-strength foamed shoe material and a preparation method thereof. Background Art
[0002] In recent years, with the advancement of material technology, many manufacturers have also begun to innovate in the field of shoe materials. Generally, shoes include uppers, midsoles and outsoles. The role of the midsole is to provide stability, cushioning and rebound, absorb the impact generated during exercise, and provide a comfortable foot feel and safety protection.
[0003] The main midsole materials are EVA, TPU, POE, EDPM, etc. The general foaming method is to mix the raw materials with foaming agents and accelerators and other additives to form granules, and then use molds to foam at high temperature and high pressure, which is chemical foaming. In recent years, more and more manufacturers have used supercritical foaming technology. Compared with traditional chemical foaming, supercritical foaming has obvious advantages. Carbon dioxide gas or nitrogen is used as a physical foaming agent. These fluids dissolve and diffuse into the polymer matrix under high temperature and high pressure, and then the gas is precipitated through rapid pressure relief to form a micro-nano size and high pore density pore structure, which can simultaneously provide support, cushioning and maintain lightness, and is widely favored by consumers.
[0004] Some foam shoe materials are prone to wrinkles and deformation during use because their compression permanent deformation rate is too large. It is necessary to increase the fatigue resistance and resilience of the foam shoe materials. Summary of the invention
[0005] The object of the present invention is to provide a high-strength foamed shoe material and a preparation method thereof, and to improve the resilience of the foamed shoe material and reduce its compression permanent deformation through raw material matching.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing a high-strength foamed shoe material comprises the following steps:
[0008] EVA elastomer, polyether block polyamide elastomer, EVA-g-MAH elastomer, polyurea elastomer, reinforcing fiber and nucleating agent are mixed in a mass ratio of 60-70:25-30:8-12:5-8:5-6:0.5-0.8, and then extruded into granules by a twin-screw extruder. After obtaining foamed particles, they are injection-molded into a mold by an injection machine for pressure-maintaining molding to obtain a shoe material blank. The shoe material blank is placed in a foaming kettle, and foamed by supercritical foaming at a pressure of 25-28 MPa and a temperature of 145-150° C. using nitrogen as a supercritical gas, and a high-strength foamed shoe material is obtained after the pressure is released.
[0009] Furthermore, the nucleating agent is any one of nano titanium dioxide, nano zinc oxide and nano calcium carbonate.
[0010] Further, the reinforcing fiber is prepared by the following steps:
[0011] Step 1: Add bio-based lignin, polyethylene glycol 400 and propylene glycol into a reactor in a mass ratio of 1:2:1 and stir to mix, then add 98% sulfuric acid by mass into the reactor, stir and react for 1.2-1.5 hours at 130-140°C and 200-300r / min, cool naturally, adjust the pH value of the reaction solution to neutral with sodium hydroxide solution, remove water by rotary evaporation, and obtain bio-based lignin polyol.
[0012] Step 2: Add isophorone diisocyanate, bio-based lignin polyol and dibutyltin dilaurate into a reaction kettle, stir and mix, then keep warm at 45-50° C. for 20-24 hours, wash the cured product with anhydrous ethanol 2-3 times, and vacuum dry to obtain polyhydroxy lignin polyurethane.
[0013] Step three: add urea-containing polyimide and polyhydroxy lignin polyurethane into a reactor and dissolve them with dimethyl sulfoxide, filter through a copper mesh to obtain a spinning solution, prepare the spinning solution into a nanofiber membrane by an electrospinning method, crush the nanofiber membrane, and use a high-speed homogenizer to break up and evenly disperse the nanofibers to obtain reinforced fibers with a length of 1±0.2 mm.
[0014] Furthermore, the mass ratio of isophorone diisocyanate, bio-based lignin polyol and dibutyltin dilaurate is 20:30-32:0.3.
[0015] Furthermore, the usage ratio of the urea-containing polyimide, the polyhydroxy lignin polyurethane and the dimethyl sulfoxide is 10 g: 4-5 g: 50 mL.
[0016] Furthermore, the specific steps of the electrospinning method are: at an ambient temperature of 20-25°C and an ambient humidity of 40%, the spinning solution is spun using an electrospinning device at a spinning voltage of 20-22kV, the spinning solution flow rate is 1-1.2mL / h, the roller receiving distance is 18-20cm, and the roller speed is 450r / min.
[0017] Further, the polyimide containing urea groups is prepared by the following steps:
[0018] Step 1: Add 4,4'-diaminodiphenyl ether and N,N-dimethylacetamide to a reactor, stir at 200-300 r / min for 15-20 min, add biphenyltetracarboxylic acid dianhydride to the reactor, stir and react at 30-35° C. for 4.5-5 h to obtain an amino-terminated polyamic acid solution; the dosage ratio of 4,4'-diaminodiphenyl ether, N,N-dimethylacetamide and biphenyltetracarboxylic acid dianhydride is 20 g: 250 mL: 27.3-27.6 g.
[0019] Step 2: Add 4,4'-diaminodiphenyl ether and N,N-dimethylacetamide to the reactor, stir at 200-300 r / min for 15-20 min, add isophorone diisocyanate and dibutyltin dilaurate to the reactor, stir and react at 70-75° C. for 4.5-5 h to obtain an isocyanate-terminated polyurea solution; the dosage ratio of 4,4'-diaminodiphenyl ether, N,N-dimethylacetamide, isophorone diisocyanate and dibutyltin dilaurate is 20 g: 250 mL: 23.3-24.4 g: 0.3 g.
[0020] Step 3: Add the amino-terminated polyamic acid solution and the isocyanate-terminated polyurea solution into a reaction kettle, stir and mix, react at 70-75° C. for 1-1.2 hours, then add biphenyltetracarboxylic dianhydride as a cross-linking agent into the reaction kettle, continue to react for 4-4.5 hours to obtain a polyamic acid solution containing urea groups, remove the solvent by rotary evaporation, imide the product at 200-220° C. for 6-8 hours, wash with anhydrous ethanol and deionized water for 2-3 times respectively, and dry to obtain a polyimide containing urea groups.
[0021] Furthermore, the usage ratio of the amino-terminated polyamic acid solution, the isocyanate-terminated polyurea solution and the biphenyltetracarboxylic dianhydride is 250 mL: 75-100 mL: 1.2-1.6 g.
[0022] Further, the polyurea elastomer is prepared by the following steps:
[0023] Add 4,4'-diaminodiphenyl ether and N,N-dimethylacetamide to the reactor, stir at 200-300 r / min for 15-20 min, add isophorone diisocyanate and dibutyltin dilaurate to the reactor, stir and react at 70-75° C. for 4.5-5 h to obtain an amino-terminated prepolymer solution, then add carbon disulfide to the reactor, continue stirring and reacting for 30-40 min, remove the solvent by rotary evaporation, wash the product with anhydrous ethanol and deionized water for 2-3 times respectively, and dry to obtain a polyurea elastomer.
[0024] Furthermore, the usage ratio of 4,4'-diaminodiphenyl ether, N,N-dimethylacetamide, isophorone diisocyanate, dibutyltin dilaurate and carbon disulfide is 40g:250-300mL:22.2g:0.3-0.35g:7.6g.
[0025] Beneficial effects of the present invention:
[0026] The raw materials of the high-strength foamed shoe material of the present invention include EVA elastomer, polyether block polyamide elastomer, EVA-g-MAH elastomer, polyurea elastomer, reinforcing fiber and nucleating agent, wherein the EVA elastomer provides lightness and cushioning performance, the polyether block polyamide elastomer provides wear resistance and impact resistance, and ensures that the foamed shoe material maintains elasticity and flexibility at low temperatures, the EVA-g-MAH elastomer improves the compatibility and adhesion of the raw material parts, the polyurea elastomer helps to improve the tear strength of the foamed shoe material, and the reinforcing fiber helps to improve the mechanical strength of the material.
[0027] The reinforcing fiber of the present invention can improve the strength and toughness of the foamed shoe material. The raw materials include polyimide containing urea groups and polyhydroxy lignin polyurethane. Adding polyhydroxy lignin polyurethane can improve the flexibility of the reinforcing fiber and help reduce the increase in the hardness of the foamed shoe material. The large amount of hydroxyl groups contained in the hydroxy lignin polyurethane can react with maleic anhydride in the EVA-g-MAH elastomer during the foaming process, which helps to improve the compatibility of the reinforcing fiber and the matrix, reduce the formation of the interface layer between the nanofiber and the shoe material matrix material, avoid affecting the formation of the bubble core, make the pores evenly distributed, and thus avoid affecting the resilience of the foamed shoe material.
[0028] The polyurea elastomer of the present invention contains thiourea groups and urea groups, which are not only combined with each other in the form of hydrogen bonds, but the thiourea groups therein can also form hydrogen bonds with the urea groups in the reinforcing fibers, thereby playing a self-repairing role and helping to enhance the fatigue resistance, resilience and tear strength of the foamed shoe material. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0030] Embodiment 1: This embodiment provides a high-strength foamed shoe material, which is prepared by the following steps:
[0031] S1: Add 20 kg of 4,4'-diaminodiphenyl ether and 250 L of N,N-dimethylacetamide to a reactor, stir at 200 r / min for 15 min, add 27.3 kg of biphenyltetracarboxylic dianhydride to the reactor, stir and react at 30°C for 4.5 h to obtain an amino-terminated polyamide acid solution; add 20 kg of 4,4'-diaminodiphenyl ether and 250 L of N,N-dimethylacetamide to the reactor, stir at 200 r / min for 15 min, add 23.3 kg of isophorone diisocyanate and 0.3 kg of dibutyltin dilaurate to the reactor, stir and react at 70°C for 4.5 h to obtain an isocyanate-terminated polyurea solution.
[0032] S2: Add 250L of amino-terminated polyamic acid solution and 75L of isocyanate-terminated polyurea solution into a reactor, stir and mix, react at 70°C for 1h, then add 1.2kg of biphenyltetracarboxylic dianhydride as a cross-linking agent into the reactor, continue to react for 4h to obtain a polyamic acid solution containing urea groups, remove the solvent by rotary evaporation, imide the product at 200°C for 6h, wash twice with anhydrous ethanol and deionized water respectively, and dry to obtain a polyimide containing urea groups.
[0033] S3: Add bio-based lignin, polyethylene glycol 400 and propylene glycol into a reactor in a mass ratio of 1:2:1 and stir to mix, then add 98% sulfuric acid into the reactor, stir and react at 130°C and 200r / min for 1.2h, cool naturally, adjust the pH value of the reaction solution to neutral with sodium hydroxide solution, and remove water by rotary evaporation to obtain bio-based lignin polyol; add 20kg of isophorone diisocyanate, 30kg of bio-based lignin polyol and 0.3kg of dibutyltin dilaurate into the reactor and stir to mix, then keep warm at 45°C for 20h, wash the cured product twice with anhydrous ethanol, and vacuum dry to obtain polyhydroxy lignin polyurethane.
[0034] S4: 10kg of urea-containing polyimide and 4-5kg of polyhydroxy lignin polyurethane are added into a reactor and dissolved with 50L of dimethyl sulfoxide. After filtering through a copper mesh, a spinning solution is obtained, and the spinning solution is prepared into a nanofiber membrane by an electrospinning method. The specific steps of the electrospinning method are: at an ambient temperature of 20°C and an ambient humidity of 40%, the spinning solution is spun using an electrospinning device at a spinning voltage of 20kV, with a spinning solution flow rate of 1mL / h, a drum receiving distance of 18cm, and a drum speed of 450r / min; after the nanofiber membrane is crushed, the nanofibers are broken and evenly dispersed using a high-speed homogenizer to obtain reinforced fibers with a length of 1±0.2mm.
[0035] S5: Add 40 kg of 4,4'-diaminodiphenyl ether and 250-300 L of N,N-dimethylacetamide to the reactor, stir at 200 r / min for 15 min, add 22.2 kg of isophorone diisocyanate and 0.3 kg of dibutyltin dilaurate to the reactor, stir and react at 70°C for 4.5 h to obtain an amino-terminated prepolymer solution, then add 7.6 kg of carbon disulfide to the reactor, continue stirring and reacting for 30 min, remove the solvent by rotary evaporation, wash the product twice with anhydrous ethanol and deionized water respectively, and dry to obtain a polyurea elastomer.
[0036] S6: 60kg of EVA elastomer, 25kg of polyether block polyamide elastomer, 8kg of EVA-g-MAH elastomer, 5kg of the polyurea elastomer in step S5, 5kg of the reinforcing fiber in step S4 and 0.5kg of nano titanium dioxide are mixed and kneaded, and then extruded and granulated by a twin-screw extruder to obtain foamed particles, and then injection-molded into a mold by an injection molding machine to obtain a shoe material blank, which is placed in a foaming kettle, and foamed by supercritical foaming at a pressure of 25 MPa and a temperature of 145°C using nitrogen as a supercritical gas, and a high-strength foamed shoe material is obtained after the pressure is released.
[0037] Embodiment 2: This embodiment provides a high-strength foamed shoe material, which is prepared by the following steps:
[0038] S1: Add 20 kg of 4,4'-diaminodiphenyl ether and 250 L of N,N-dimethylacetamide to the reactor, stir at 250 r / min for 18 min, add 27.45 kg of biphenyltetracarboxylic dianhydride to the reactor, stir and react at 32°C for 4.8 h to obtain an amino-terminated polyamide acid solution; add 20 kg of 4,4'-diaminodiphenyl ether and 250 L of N,N-dimethylacetamide to the reactor, stir at 250 r / min for 18 min, add 23.85 kg of isophorone diisocyanate and 0.3 kg of dibutyltin dilaurate to the reactor, stir and react at 72°C for 4.8 h to obtain an isocyanate-terminated polyurea solution.
[0039] S2: Add 250L of amino-terminated polyamic acid solution and 85L of isocyanate-terminated polyurea solution into a reactor, stir and mix, react at 72°C for 1.1h, then add 1.4kg of biphenyltetracarboxylic dianhydride as a cross-linking agent into the reactor, continue to react for 4.2h to obtain a polyamic acid solution containing urea groups, remove the solvent by rotary evaporation, imide the product at 210°C for 7h, wash twice with anhydrous ethanol and deionized water respectively, and dry to obtain a polyimide containing urea groups.
[0040] S3: Add bio-based lignin, polyethylene glycol 400 and propylene glycol into a reactor in a mass ratio of 1:2:1 and stir to mix, then add 98% sulfuric acid into the reactor, stir and react at 135°C and 250r / min for 1.35h, cool naturally, adjust the pH value of the reaction solution to neutral with sodium hydroxide solution, and remove water by rotary evaporation to obtain bio-based lignin polyol; add 20kg of isophorone diisocyanate, 31kg of bio-based lignin polyol and 0.3kg of dibutyltin dilaurate into the reactor and stir to mix, then keep warm at 48°C for 22h, wash the cured product twice with anhydrous ethanol, and vacuum dry to obtain polyhydroxy lignin polyurethane.
[0041] S4: 10kg of urea-containing polyimide and 4.5kg of polyhydroxy lignin polyurethane are added into a reactor and dissolved with 50L of dimethyl sulfoxide. After filtering through a copper mesh, a spinning solution is obtained, and the spinning solution is prepared into a nanofiber membrane by an electrospinning method. The specific steps of the electrospinning method are as follows: at an ambient temperature of 22°C and an ambient humidity of 40%, the spinning solution is spun using an electrospinning device at a spinning voltage of 21kV, with a spinning solution flow rate of 1.1mL / h, a drum receiving distance of 19cm, and a drum speed of 450r / min; after the nanofiber membrane is crushed, the nanofibers are broken and evenly dispersed using a high-speed homogenizer to obtain reinforced fibers with a length of 1±0.2mm.
[0042] S5: Add 40 kg of 4,4'-diaminodiphenyl ether and 280 L of N,N-dimethylacetamide to the reactor, stir at 250 r / min for 18 min, add 22.2 kg of isophorone diisocyanate and 0.32 kg of dibutyltin dilaurate to the reactor, stir and react at 72°C for 4.8 h to obtain an amino-terminated prepolymer solution, then add 7.6 kg of carbon disulfide to the reactor, continue stirring and reacting for 35 min, remove the solvent by rotary evaporation, wash the product twice with anhydrous ethanol and deionized water respectively, and dry to obtain a polyurea elastomer.
[0043] S6: 65 kg of EVA elastomer, 28 kg of polyether block polyamide elastomer, 10 kg of EVA-g-MAH elastomer, 6.5 kg of the polyurea elastomer in step S5, 5.5 kg of the reinforcing fiber in step S4 and 0.65 kg of nano zinc oxide are mixed and extruded into granules by a twin-screw extruder, and foamed particles are obtained. After that, they are injection-molded into a mold by an injection molding machine and pressure-held molding is performed to obtain a shoe material blank. The shoe material blank is placed in a foaming kettle, and foamed by supercritical foaming at a pressure of 26.5 MPa and a temperature of 148° C. using nitrogen as a supercritical gas, and a high-strength foamed shoe material is obtained after the pressure is released.
[0044] Embodiment 3: This embodiment provides a high-strength foamed shoe material, which is prepared by the following steps:
[0045] S1: Add 20 kg of 4,4'-diaminodiphenyl ether and 250 L of N,N-dimethylacetamide to a reactor, stir at 300 r / min for 20 min, add 27.6 kg of biphenyltetracarboxylic dianhydride to the reactor, stir and react at 35°C for 5 h to obtain an amino-terminated polyamide acid solution; add 20 kg of 4,4'-diaminodiphenyl ether and 250 L of N,N-dimethylacetamide to the reactor, stir at 300 r / min for 15-20 min, add 24.4 kg of isophorone diisocyanate and 0.3 kg of dibutyltin dilaurate to the reactor, stir and react at 75°C for 5 h to obtain an isocyanate-terminated polyurea solution.
[0046] S2: Add 250L of amino-terminated polyamic acid solution and 100L of isocyanate-terminated polyurea solution into a reactor, stir and mix, react at 75°C for 1.2h, then add 1.6kg of biphenyltetracarboxylic dianhydride as a cross-linking agent into the reactor, continue to react for 4.5h to obtain a polyamic acid solution containing urea groups, remove the solvent by rotary evaporation, imide the product at 220°C for 8h, wash with anhydrous ethanol and deionized water for 3 times respectively, and dry to obtain a polyimide containing urea groups.
[0047] S3: Add bio-based lignin, polyethylene glycol 400 and propylene glycol into a reactor in a mass ratio of 1:2:1 and stir to mix, then add 98% sulfuric acid into the reactor, stir and react at 140°C and 300r / min for 1.5h, cool naturally, adjust the pH value of the reaction solution to neutral with sodium hydroxide solution, and remove water by rotary evaporation to obtain bio-based lignin polyol; add 20kg of isophorone diisocyanate, 32kg of bio-based lignin polyol and 0.3kg of dibutyltin dilaurate into the reactor and stir to mix, then keep warm at 50°C for 24h, wash the cured product with anhydrous ethanol 3 times, and vacuum dry to obtain polyhydroxy lignin polyurethane.
[0048] S4: 10kg of urea-containing polyimide and 5kg of polyhydroxy lignin polyurethane are added into a reactor and dissolved with 50L of dimethyl sulfoxide. After filtering through a copper mesh, a spinning solution is obtained, and the spinning solution is prepared into a nanofiber membrane by an electrospinning method. The specific steps of the electrospinning method are: at an ambient temperature of 25°C and an ambient humidity of 40%, the spinning solution is spun using an electrospinning device at a spinning voltage of 22kV, with a spinning solution flow rate of 1.2mL / h, a drum receiving distance of 20cm, and a drum speed of 450r / min; after the nanofiber membrane is crushed, the nanofibers are broken and evenly dispersed using a high-speed homogenizer to obtain reinforced fibers with a length of 1±0.2mm.
[0049] S5: Add 40 kg of 4,4'-diaminodiphenyl ether and 300 L of N,N-dimethylacetamide to the reactor, stir at 300 r / min for 20 min, add 22.2 kg of isophorone diisocyanate and 0.35 kg of dibutyltin dilaurate to the reactor, stir and react at 75°C for 5 h to obtain an amino-terminated prepolymer solution, then add 7.6 kg of carbon disulfide to the reactor, continue stirring and reacting for 40 min, remove the solvent by rotary evaporation, wash the product with anhydrous ethanol and deionized water for 3 times respectively, and dry to obtain a polyurea elastomer.
[0050] S6: 70kg of EVA elastomer, 30kg of polyether block polyamide elastomer, 12kg of EVA-g-MAH elastomer, 8kg of the polyurea elastomer in step S5, 6kg of the reinforcing fiber in step S4 and 0.8kg of nano calcium carbonate are mixed and kneaded, and then extruded and granulated by a twin-screw extruder to obtain foamed particles, and then injection-molded into a mold by an injection molding machine to obtain a shoe material blank, which is placed in a foaming kettle, and foamed by supercritical foaming at a pressure of 28 MPa and a temperature of 150° C. using nitrogen as a supercritical gas, and a high-strength foamed shoe material is obtained after the pressure is released.
[0051] Comparative Example 1: Based on Example 3, no polyurea elastomer was added, and the other steps remained unchanged to prepare a foamed shoe material.
[0052] Comparative Example 2: Based on Example 3, no reinforcing fiber was added, and the other steps remained unchanged to prepare a foamed shoe material.
[0053] Comparative Example 3: Based on Example 3, in step S4, the polyimide containing urea groups is replaced with commercially available polyimide, and the other steps remain unchanged to prepare a foamed shoe material.
[0054] In the examples and comparative examples, the EVA elastomer is Formosa Plastics 7470M from Taiwan, China; the polyether block polyamide elastomer is Pebax3533 from Arkema of France; and the EVA-g-MAH elastomer is Dow C250 from the United States.
[0055] The gas saturation time of supercritical foaming in the embodiments and comparative examples was 4.5 h, and the pressure release time was 30 s.
[0056] Samples were prepared according to the corresponding standards for different foaming materials in Examples 1 to 3 and Comparative Examples 1 to 3 and were tested for performance. The density of different samples was tested by the drainage method with reference to GB / T 6343-2009; the hardness (Shore C) of different samples was tested with reference to ISO 2439-2008; the resilience of different samples was tested by the falling ball method with reference to GB / T 6670-2008; the compression permanent deformation of different samples was tested with reference to GB / T6669-2008; and the tear strength of different samples was tested with reference to GB / T 529-2008.
[0057] The results are shown in Table 1:
[0058] Table 1
[0059] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 <![CDATA[Density (g / cm 3 )]]> 0.18 0.17 0.17 0.15 0.14 0.20 Hardness(Shore C) 45 47 48 42 43 51 Resilience(%) 73 74 72 65 69 68 Compression set (%) 15.88 15.26 15.45 24.36 19.65 22.48 Tear strength(N / mm) 13.4 13.7 13.8 11.5 10.2 13.2
[0060] As can be seen from Table 1, the foamed shoe material in Example 1-Example 3 has higher resilience and tear strength, and the compression permanent deformation rate is also lower. The reason why the resilience decreases and the compression permanent deformation increases in Comparative Example 1 is that the polyurea elastomer contains thiourea groups and urea groups, which not only combine in the form of hydrogen bonds, but also the thiourea groups can form hydrogen bonds with the urea groups in the reinforcing fibers, thereby enhancing the overall performance of the foamed shoe material. Comparative Example 2 shows that the reinforcing fibers can improve the resilience and tear strength of the foamed shoe material, and the reinforcing fiber raw materials include polyimide and polyhydroxy lignin polyurethane containing urea groups, wherein the urea groups can be cross-linked with the thiourea groups in the polyurea elastomer by hydrogen bonds, and Comparative Example 3 shows that the large amount of hydroxyl groups contained in the polyhydroxy lignin polyurethane can improve the compatibility of the reinforcing fibers and the matrix, reduce the formation of the interface layer between the nanofiber and the shoe material matrix material, avoid affecting the formation of the bubble core, and make the pores evenly distributed, thereby avoiding affecting the resilience of the foamed shoe material.
[0061] It should be noted that, in this article, terms such as "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0062] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high-strength foamed shoe material, characterized in that: The steps include: EVA elastomer, polyether block polyamide elastomer, EVA-g-MAH elastomer, polyurea elastomer, reinforcing fiber and nucleating agent are mixed in a mass ratio of 60-70:25-30:8-12:5-8:5-6:0.5-0.8, and then extruded into granules by a twin-screw extruder, and then foamed particles are injected into a mold by an injection molding machine to obtain a shoe material blank, and the shoe material blank is placed in a foaming kettle, and nitrogen is used as a supercritical gas, and a supercritical foaming method is used for foaming at a pressure of 25-28MPa and a temperature of 145-150°C, and a high-strength foamed shoe material is obtained after the pressure is released; The nucleating agent is any one of nano titanium dioxide, nano zinc oxide and nano calcium carbonate; The reinforcing fiber is prepared by the following steps: Polyimide and polyhydroxy lignin polyurethane containing urea groups are added to a reactor and dissolved in dimethyl sulfoxide. The spinning solution is obtained after filtering through a copper mesh. The spinning solution is prepared into a nanofiber membrane by an electrospinning method. The nanofiber membrane is crushed and the nanofibers are broken and evenly dispersed using a high-speed homogenizer to obtain reinforced fibers with a length of 1±0.2 mm.
2. The method for preparing a high-strength foamed shoe material according to claim 1, characterized in that: The polyhydroxy lignin polyurethane is prepared by the following steps: Isophorone diisocyanate, bio-based lignin polyol and dibutyltin dilaurate are added into a reaction kettle and stirred and mixed, and then kept warm at 45-50°C for 20-24h, and the solidified product is washed with anhydrous ethanol for 2-3 times and vacuum dried to obtain polyhydroxy lignin polyurethane; the amount ratio of the urea-containing polyimide, polyhydroxy lignin polyurethane and dimethyl sulfoxide is 10g:4-5g:50mL.
3. The method for preparing a high-strength foamed shoe material according to claim 2, characterized in that: The mass ratio of isophorone diisocyanate, bio-based lignin polyol and dibutyltin dilaurate is 20:30-32:0.
3.
4. The method for preparing a high-strength foamed shoe material according to claim 2, characterized in that: The bio-based lignin polyol is prepared by the following steps: Bio-based lignin, polyethylene glycol 400 and propylene glycol are added into a reactor in a mass ratio of 1:2:1 and stirred and mixed, and then sulfuric acid with a mass fraction of 98% is added dropwise into the reactor, and the reaction is stirred for 1.2-1.5 hours at 130-140° C. and 200-300 r / min, and the reaction is naturally cooled, and the pH value of the reaction solution is adjusted to be neutral with a sodium hydroxide solution, and water is removed by rotary evaporation to obtain a bio-based lignin polyol.
5. The method for preparing a high-strength foamed shoe material according to claim 1, characterized in that: The specific steps of the electrospinning method are: at an ambient temperature of 20-25°C and an ambient humidity of 40%, the spinning solution is spun using an electrospinning device at a spinning voltage of 20-22kV, the spinning solution flow rate is 1-1.2mL / h, the roller receiving distance is 18-20cm, and the roller speed is 450r / min.
6. The method for preparing a high-strength foamed shoe material according to claim 1, characterized in that: The polyimide containing urea groups is prepared by the following steps: Adding an amino-terminated polyamic acid solution and an isocyanate-terminated polyurea solution into a reaction kettle, stirring and mixing, reacting at 70-75° C. for 1-1.2 hours, then adding biphenyltetracarboxylic dianhydride as a crosslinking agent into the reaction kettle, continuing the reaction for 4-4.5 hours to obtain a polyamic acid solution containing urea groups, rotary evaporation to remove the solvent, imidizing the product at 200-220° C. for 6-8 hours, washing with anhydrous ethanol and deionized water for 2-3 times respectively, and drying to obtain a polyimide containing urea groups; The usage ratio of the amino-terminated polyamic acid solution, the isocyanate-terminated polyurea solution and the biphenyltetracarboxylic dianhydride is 250 mL: 75-100 mL: 1.2-1.6 g.
7. The method for preparing a high-strength foamed shoe material according to claim 6, characterized in that: The amino-terminated polyamic acid solution is prepared by the following steps: Add 4,4'-diaminodiphenyl ether and N,N-dimethylacetamide to the reaction kettle, stir at 200-300 r / min for 15-20 min, add biphenyltetracarboxylic dianhydride to the reaction kettle, stir and react at 30-35° C. for 4.5-5 h to obtain an amino-terminated polyamic acid solution; the dosage ratio of 4,4'-diaminodiphenyl ether, N,N-dimethylacetamide and biphenyltetracarboxylic dianhydride is 20 g: 250 mL: 27.3-27.6 g.
8. The method for preparing a high-strength foamed shoe material according to claim 6, characterized in that: The isocyanate-terminated polyurea solution is prepared by the following steps: Add 4,4'-diaminodiphenyl ether and N,N-dimethylacetamide to the reaction kettle, stir at 200-300 r / min for 15-20 min, add isophorone diisocyanate and dibutyltin dilaurate to the reaction kettle, stir and react at 70-75° C. for 4.5-5 h to obtain an isocyanate-terminated polyurea solution; the dosage ratio of 4,4'-diaminodiphenyl ether, N,N-dimethylacetamide, isophorone diisocyanate and dibutyltin dilaurate is 20 g: 250 mL: 23.3-24.4 g: 0.3 g.
9. The method for preparing a high-strength foamed shoe material according to claim 1, characterized in that: The polyurea elastomer is prepared by the following steps: Add 4,4'-diaminodiphenyl ether and N,N-dimethylacetamide to the reaction kettle, stir at 200-300 r / min for 15-20 min, add isophorone diisocyanate and dibutyltin dilaurate to the reaction kettle, stir and react at 70-75° C. for 4.5-5 h to obtain an amino-terminated prepolymer solution, then add carbon disulfide to the reaction kettle, continue stirring and reacting for 30-40 min, remove the solvent by rotary evaporation, wash the product with anhydrous ethanol and deionized water for 2-3 times respectively, and dry to obtain a polyurea elastomer; The usage ratio of the 4,4'-diaminodiphenyl ether, N,N-dimethylacetamide, isophorone diisocyanate, dibutyltin dilaurate and carbon disulfide is 40g: 250-300mL: 22.2g: 0.3-0.35g: 7.6g.
10. A high-strength foamed shoe material, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Liquefaction modified lignin filling-type polyurethane foaming glue
CN106220807A
Polyimide ultra-short fiber and preparation method thereof
CN107675288A
Polyurea-polyimide block copolymer molding powder and preparation method thereof
CN109942825A
Degradable foaming shoe insole material and preparation method thereof
CN116925460A
Reinforced polymer matrix and product containing micro and macro reinforcement
US5225457A
